Hubungan Antara Kecerdasan Emoisonal dengan Stress Pada Remaja Putra - Rayhanun Hidayati; Dewi Rayani; Reza Zulaifi (Lembaga Kajian Ilmu Pengetahuan dan Publikasi Indonesia, 2025)
The purpose of this research is to determine the correlation stress and emotional intelligence in adolescents. Adolescence is known as the transition period, the transition period between children and adults. During this period, many changes occur, both physical and psychological, which can cause stress for teenagers. The data collection method uses the questionnaire method as the main method, observation, interviews and documentation as complementary methods. The research sample was 66 students from a total population of 133 students, data analysis using the product moment coefficient correlation formula. As for the results of data analysis, the rxy value was at (0.33), while for the rtable value at the 0.05 significance level it was (0.239). Because rcount > rtable (0.33 > 0.239), this means that Ho is rejected and Ha is accepted. So the results of this research show that there is a relationship between emotional intelligence and stress in adolescents at MA NW Putra Narmada . Significant